Methodological principles of electromagnetic screens application for public protection from electromagnetic field and radiation - Gliva, V.; Panova, O.; Voloshkina, O. (My University, 2016)
The growing levels of electromagnetic fields require the improvement of protective shielding methods. Frequency and amplitude parameters of fields have been analyzed according to national and international standards of electromagnetic safety and guidelines on shielding application have been given. The methodological principles of choosing and applying electromagnetic screens depending on radiation parameters and the required protection efficiency have been developed.
Keywords: shielding; electromagnetic field; reflection coefficient